Procuring donors: how government contracts affect campaign contributions - Schneider, Daniel Castanheira (2024)
This paper studies the relationship between public procurement and private funding of political campaign under a different perspective with respect to the existing literature. While most studies are concerned with the phenomenon of favoritism in the allocation of government contracts to politically connected agents, we investigate how firms’ donations to political campaigns respond to the outcomes of competitive procurement procedures. Using data on municipal tenders taking place the state of São Paulo, Brazil, in the context of the engineering and construction sector, we employ a regression discontinuity strategy to identify the effect of winning an additional contract on firms’ donation outcomes. We find that the probability of donating increases by 5 to 10 percentage points after a firm wins its first contract. We also show that this effect is stronger and concentrated in those contracts of higher value, and not restricted to a specific group of municipalities within the state. Results on incremental contracts (i.e. winning a second, third or fourth tender), however, are inconclusive.